Democracy and reforms - Paola Giuliano; Prachi Mishra; Antonio Spilimbergo (Institute for the Study of Labor (IZA), 2009)
Empirical evidence on the relationship between democracy and economic reforms is scarce, limited to few reforms and countries and for few years. This paper studies the impact of democracy on the adoption of economic reforms using a new dataset on reforms in the financial, capital, public, and banking sectors, product and labor markets, agriculture, and trade for 150 countries over the period 1960-2004. Democracy has a positive and significant impact on the adoption of economic reforms but there is no evidence that economic reforms foster democracy. Our results are robust to the inclusion of a large variety of controls and estimation strategies.
urn:nbn:de:101:1-20090306256
Keywords: O57; E6; 330; Political economy; transition; economic liberalization; Wirtschaftsreform; Deregulierung; Demokratie; Public Choice; Welt